1992
DOI: 10.1177/0734242x9201000204
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Behaviour of Municipal Solid Waste Incinerator Bottom Ash in Monofills

Abstract: A method is presented to predict the short-term (months to years) and long-term (> 30 years) chemical behaviour of bottom ash from municipal solid waste incinerators in monofills. It is based on bottom ash composition and laboratory kinetic studies of bottom ash with water. Bottom ash after the quench tank is a reactive mixture in which slow and fast acid/base reactions occur. These intrinsic acid/base reactions continue for at least several months, and the end point is not yet known. The heavy metal concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(36 citation statements)
references
References 1 publication
0
36
0
Order By: Relevance
“…In A-type bottom ash leachates, Ca is the dominant cation; Ca concentrations increase from about 800 mg/L at pH 12 to about 5000 mg/L at pH 4 ( Figure 1a). Belevi et al (15) have shown that this mineral forms as a result of the hydrolysis of primary CaO in the bottom ash. Belevi et al (15) have shown that this mineral forms as a result of the hydrolysis of primary CaO in the bottom ash.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In A-type bottom ash leachates, Ca is the dominant cation; Ca concentrations increase from about 800 mg/L at pH 12 to about 5000 mg/L at pH 4 ( Figure 1a). Belevi et al (15) have shown that this mineral forms as a result of the hydrolysis of primary CaO in the bottom ash. Belevi et al (15) have shown that this mineral forms as a result of the hydrolysis of primary CaO in the bottom ash.…”
Section: Resultsmentioning
confidence: 99%
“…However, considerably less attention has been paid to the leaching mechanisms of (naturally) weathered MSWI bottom ash (6). The effect of quenching on MSWI bottom ash mineralogy has not been discussed much either (13,15). In short, there is a lack of systematic geochemical research on MSWI bottom ash at different stages of weathering.…”
Section: Introductionmentioning
confidence: 99%
“…TC in solid residues includes carbonate carbon (CC) and total organic carbon (TOC). TOC is defined as the difference between TC and CC (1)(2)(3). Hence, TOC is the sum of organic carbon (OC) and elemental carbon (EC).…”
Section: Introductionmentioning
confidence: 99%
“…Municipal solid waste incineration (MSWI) reduces the volume of waste by about 90% and the mass by about 70% (Abanades et al, 2002). Bottom ash, which is the residue produced in the major amount is mainly composed of Si, Fe, Ca, Mg, Al, Na and K, in the form of oxides and thus presents a similar composition to that of geological materials (Belevi et al, 1992;Kirby and Rimstidt, 1993). Bottom ash, which is the residue produced in the major amount is mainly composed of Si, Fe, Ca, Mg, Al, Na and K, in the form of oxides and thus presents a similar composition to that of geological materials (Belevi et al, 1992;Kirby and Rimstidt, 1993).…”
Section: Introductionmentioning
confidence: 99%